Modern Family Dynamics; How Millennials and Gen Z Are Shaping New Relationship Norms - Rabia Hameed; Tayyeba Ahmad; Saira Kanwal; Hassan Imran (Research Journal of Psychology, 2025)
This study aimed to examine the evolving family dynamics and relationship norms among Millennials and Gen Z, focusing on how digital communication, economic factors, and shifting societal values influenced these changes. Existing research, including studies by Twenge et al. (2021) and the Pew Research Center (2023), indicated a decline in traditional family structures and a rise in flexible living arrangements. Using a mixed-methods approach, data were collected from Millennials and Gen Z participants through surveys and interviews, and analyzed using statistical and thematic analysis. Findings revealed that Millennials largely adhered to nuclear family structures and traditional parenting roles, whereas Gen Z preferred multigenerational households, cohabitation, and non-traditional parenting. Digital communication played a critical role in maintaining family relationships, and work-life balance was prioritized by Gen Z. The study contributed to family sociology and psychology by emphasizing the growing influence of technology on relationship norms. Policy recommendations included adjustments to workplace flexibility, urban housing policies, and parental leave structures. However, the study was limited by social desirability bias and the lack of longitudinal data, restricting its ability to track long-term generational shifts. Future research should explore these trends over extended periods and incorporate diverse cultural contexts to understand global variations in modern family dynamics. This study provided theoretical and practical insights into the evolving nature of family relationships, highlighting the need for institutional adaptation to accommodate changing generational expectations.